Insight into low-temperature sintering of samarium-doped ceria mixed with scavenging lithium. (1st February 2022) - Ishii, Akihiro; Ishijima, Hibiki; Kobayashi, Kosei; Oikawa, Itaru; Takamura, Hitoshi
Graphical abstract: Image, graphical abstract Abstract: The refractory nature of oxide-ion conducting Sm-doped CeO2 (SDC) has hindered the development of SDC devices. Lithium has been found to be an excellent sintering aid that enables sintering at temperatures as low as 900 °C and also increases grain boundary conductivity. Even though Li–Si oxides melt only above the sintering temperature in reality, it is generally believed that these benefits are given by virtue of a formation of liquid phases with silicon contaminants. In this study, the key element for low-temperature sintering was revealed to be aluminum, which is spontaneously introduced into SDC by a covert but intense chemical reaction between the mixed lithium and the alumina crucible. The results show that 1 wt% lithium addition is responsible for the unintended introduction of 32 mol% aluminum. Computational thermodynamic calculations for a Li–Si–Al oxide system clarified that aluminum introduction is essential to reduce the melting point below the sintering temperature. A nano-scale analysis clearly indicates the segregation of aluminum at SDC grain-boundary triple junctions, like LiAlO2, while silicon appears to migrate towards the SDC-SDC grain boundaries as amorphous SiO2 . This suggests that the decomposition of the Li–Si–Al liquid oxide filling the grain boundaries is associated with the reflow of silicon and the loss of lithium as sintering proceeds. It was shown that zirconium is also introduced into SDC due to ball-mill processing, and that it potentially forms Li–Si–Zr oxides which remain in their solid state during sintering. The results of this study highlight the importance of taking the impact of unintended aluminum introduction into consideration for a variety of ceramics mixed with even minute quantities of lithium.